Effect of high-pressure processing and bromelain application on the quality characteristics of buffalo meat - Md Zuki, Nur Mursyidah; Kumar, Pavan; Sazili, Awis Qurni; Suryaningsih, Lilis; Utama, Dicky Tri; Mahmud Ab Rashid, Nor-Khaizura; Ismail-Fitry, Mohammad Rashedi (Malaysian Society of Applied Biology, 2025)
The present study evaluated the effect of bromelain and high-pressure processing (HPP) on the physicochemical, tenderization, and microstructure of buffalo meat. The buffalo meat samples were marinated with 5% bromelain enzyme for 24 hr at 4°C followed by HPP treatment at 0 MPa, 100 MPa, and 300 MPa for 5 min at 20 ± 2°C, leading to six samples viz Control (without bromelain and with bromelain, no high-pressure treatment), 100 MPa (with & without bromelain) and 300 MPa (with & without bromelain). The pH and moisture content of buffalo meat improved when subjected to pressure and bromelain enzyme. The cooking yield was reduced for enzyme-treated meat, while there was no significant (p>0.05) difference for HPP-treated meat. Hardness and shear force reduced at 100 and 300 MPa compared to the control; however, they were not statistically significant (p>0.05). In addition, buffalo meat that was treated with 300 MPa had a more compact but ruptured fibre structure than the control. The sensory panellists preferred non-bromelain-treated meat due to the unpleasant taste of enzyme-treated meat. In conclusion, bromelain and HPP could improve buffalo meat tenderness, but the time and pressure of HPP need to be increased to get optimal tenderness while replacing bromelain with other types of enzymes to cater for the taste of the meat sample.